ECOTOURISM DEVELOPMENT OF ISLAMIC BASED - Darmadi, Yudi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Real Work Lecture is one manifestation of Tri Dharma College namely community service. Real Work Lecture has a positive impact for the community, both in terms of development of infrastructure, economic development, education, religious and environmental hygiene. In addition, the Real Work Lecture is also has provided invaluable experience for students KKN 2016 had engaged in service learning her in Kampung Cipicung village Kabandungan districts Kabandungan Sukabumi, about how to live in the midst of society, how to socialize with people, to exchange thoughts with the public, and take on the life sciences community to incorporate economic sciences of Islam to the local community that this Cipicung village can grow in terms of local and cultural potential. By raising the local knowledge and the various tourist attractions in sub Kabandungan.